Patronage, gentility, and “base degree”: Edmund Spenser and Lord Burghley - McCabe, R (Routledge, 2017)
This essay examines the social asymmetry of Early Modern patronage by focussing on Edmund Spenser’s complex relationship with Lord Burghley. Both were anxious to validate their social credentials, the one as novus homo, and other as novus poeta. Burghley sought to offset criticism of his rise by consolidating a reputation for public service with claims of illustrious ancestry, and scores of dedicators obliged. Spenser was anxious to claim the status of gentleman through talent despite his obscure origins. In appending a dedicatory sonnet to Burghley in the 1590 Faerie Queene he endorses his public image in the hope of reciprocal acknowledgement. Apparently disappointed, he responds in Complaints (1591) by presenting Burghley as a mercenary parvenu, while for the first time claiming kinship to the “ancient” house of the Spencers of Althorp, thereby reversing the social hierarchy but problematizing his own criteria for gentility.